Continuous fiber reinforced h-bn-based composite material and its rapid and efficient preparation method and application

CN122916701APending Publication Date: 2026-10-16NAT UNIV OF DEFENSE TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611209912.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-11
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

以上方法制备氮化硼基复合材料在存在制备周期长等的问题,现有制备技术无法进一步突破h-BN基材料密度与综合性能提升,具体体现在以下几个方面:

Benefits of technology

1. 本发明的连续纤维增强h-BN基复合材料的快速高效制备方法中,采用粉体层铺预压,结合高温-高压协同作用,实现对复合材料快速高效致密化,无需进行预制三维编织件即可获得层间结合优异,剪切性能良好的纤维增强复合材料。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122916701A_ABST
    Figure CN122916701A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of boron nitride-based composite materials, and particularly discloses a continuous fiber reinforced h-BN-based composite material and a rapid and efficient preparation method and application thereof, which comprises the following steps: layering in a manner of one layer of fiber cloth and one layer of polyborazylene raw material powder, then pre-pressing to obtain a blank; performing hot-pressing sintering on the blank at 1100-1300 DEG C and under a pressure of 5-35 MPa to obtain a preliminarily dense composite material; and performing one-time impregnation of the preliminarily dense composite material in cyclic borazylene, then solidifying and cracking to obtain the continuous fiber reinforced h-BN-based composite material. In the rapid and efficient preparation method of the continuous fiber reinforced h-BN-based composite material, powder layer pre-pressing is adopted, high temperature and high pressure are combined, and the composite material is rapidly and efficiently densified, so that a fiber reinforced composite material with excellent interlayer bonding and good shearing performance can be obtained without a three-dimensional braided piece.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of boron nitride-based composite materials technology, and in particular to a continuous fiber-reinforced h-BN-based composite material and its rapid and efficient preparation method and application. Background Technology

[0002] Continuous fiber-reinforced hexagonal boron nitride (h-BN)-based composites possess excellent comprehensive properties, including high temperature resistance, high thermal conductivity, corrosion resistance, low dielectric constant, strong mechanical properties, and stable chemical properties, and have been widely used in aircraft antenna radomes. Currently, common preparation methods for h-BN-based composites include precursor impregnation pyrolysis (PIP), boric acid impregnation sintering, and chemical vapor infiltration (CVI). However, these methods suffer from long preparation cycles, and current technologies cannot further improve the density and overall performance of h-BN-based materials, specifically in the following aspects: First, existing technologies generally require three-dimensional weaving of fibers to ensure interlayer bonding strength in order to obtain composite materials with good shear properties, which is costly and time-consuming. For example, researchers such as Zou Chunrong (Preparation and performance study of nitride fiber reinforced boron nitride ceramic matrix wave-transparent composite materials) and Li Bin (Preparation and performance study of nitride ceramic matrix ablation-resistant and wave-transparent composite materials and their radomes) have used 2.5D fiber braided parts as the reinforcing phase of composite materials, which is costly and complex in process.

[0003] Secondly, existing technologies have very long preparation cycles for h-BN matrices. For example, the PIP process typically requires 5-8 PIP cycles to obtain materials that meet the application requirements. Chemical vapor deposition (CVD) has a very slow densification rate, approximately 1-2 mm / day, and is prone to surface crusting that prevents the filling of internal pores. Li Junsheng's research on the synthesis and conversion of boron azazine to prepare boron nitride, using CVD to prepare BN, achieved the fastest deposition rate at 1000 ℃, but even that was only about 1 μm / h.

[0004] Third, existing technologies struggle to overcome the density limitations of composite materials, thus restricting improvements in their mechanical and antioxidant properties and limiting their applications. Li Duan from the National University of Defense Technology (Preparation and Performance Study of Boron Nitride Fiber Reinforced Ceramic Matrix Wave-Transparent Composites) used polyboronazine precursors to prepare BN... f / BN-based composite materials have a density of only 1.60 g / cm³. 3 Flexural strength 53.8 MPa.

[0005] In summary, existing fiber-reinforced h-BN matrix composites suffer from problems such as long preparation cycles, low density, and the need for three-dimensional weaving of the fiber cloth to improve interlayer bonding. Researching a rapid and efficient method for preparing continuous fiber-reinforced h-BN matrix composites, and a method that can improve interlayer properties without relying on three-dimensional weaving, is of great significance for promoting the application of fiber-reinforced h-BN matrix composites. Summary of the Invention

[0006] To address the above shortcomings, this invention provides a continuous fiber-reinforced h-BN matrix composite material and its rapid and efficient preparation method and application. It designs an HP (hot pressing sintering) + PIP (precursor impregnation pyrolysis) preparation technology (precursor impregnation pyrolysis assisted hot pressing sintering). Hot pressing sintering is used to prepare the matrix between fiber bundles, and a subsequent PIP process further fills the small pores within the fiber bundles. This achieves rapid preparation of high-density, high-strength composite materials without the need for three-dimensional fiber weaving. The specific technical solution is as follows: A rapid and efficient method for preparing continuous fiber-reinforced h-BN-based composite materials includes the following steps: (1) Add the polyboronazine powder to a solvent and ball mill it, then vacuum dry it to obtain the raw material powder; (2) Lay out layers of fiber cloth and raw material powder obtained in step (1) one layer at a time, and then pre-press to obtain a blank; (3) The blank obtained in step (2) is hot-pressed and sintered at 1100-1300℃ and 5~35MPa pressure to obtain a preliminary dense composite material; (4) The preliminarily dense composite material obtained in step (3) is impregnated once in cycloborane, and then cured and pyrolyzed to obtain a continuous fiber reinforced h-BN-based composite material.

[0007] In the optimized preparation method described above, in step (1), the ball milling speed is 400-600 rpm, the ball milling time is 10-15 h, and the particle size D50 of the raw material powder after ball milling is <2 μm. In the optimized preparation method described above, the fiber cloth is made of alumina, silicon nitride, or silicon boron nitride fiber cloth.

[0008] In the optimized preparation method described above, in step (2), the density of the powder layer is 0.08~0.11 g / cm³. 2 The volume fraction of the fiber cloth is 20-30%.

[0009] In the optimized preparation method described above, the pre-compression pressure in step (2) is 4~7 MPa.

[0010] In the optimized preparation method described above, in step (3), hot pressing sintering is carried out in a protective atmosphere, and the holding and pressing time during the sintering process is 1~4 h, and the heating rate is 5~10℃ / min.

[0011] In the optimized preparation method described above, the protective atmosphere is nitrogen.

[0012] In the optimized preparation method described above, in step (4), after curing and pyrolysis at 90~120℃ for 20~40 h, high-temperature pyrolysis at 1200~1350℃ for 0.5~2 h is performed.

[0013] On the other hand, the present invention also provides a continuous fiber reinforced h-BN-based composite material, which is prepared by the above-described preparation method.

[0014] In the optimized continuous fiber reinforced h-BN matrix composite material described above, the fiber volume fraction of the composite material is 20-30%, and the density is >1.7 g / cm³. 3 Flexural strength > 90 MPa, shear strength > 17 MPa.

[0015] On the other hand, the present invention also provides the application of the above-mentioned continuous fiber reinforced h-BN matrix composite material in the manufacture of a transparent antenna radome or a transparent antenna window.

[0016] Compared with the prior art, the beneficial effects of the present invention are: 1. In the rapid and efficient preparation method of continuous fiber reinforced h-BN matrix composite material of the present invention, powder layering and pre-compression are adopted, combined with high temperature and high pressure synergy, to achieve rapid and efficient densification of composite material. Fiber reinforced composite material with excellent interlayer bonding and good shear performance can be obtained without prefabricating three-dimensional braided parts.

[0017] 2. This invention uses powder layering and hot pressing sintering as the main means of densifying composite materials. By utilizing a force-thermal coupling method, compared with existing preparation technologies, it can significantly shorten the material preparation cycle and obtain high-density, high-performance composite materials.

[0018] 3. This invention utilizes precursor impregnation pyrolysis-assisted hot pressing sintering to complete the filling of small pores within the bundle, further improving the compactness of the composite material. Attached Figure Description

[0019] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0020] Figure 1 XCT reconstruction images of the h-BN-based composite materials prepared in Example 2 and the comparative example of the present invention: (a) Example 2, (b) comparative example; (c) fiber, matrix and pore ratio of Example 2 and the comparative example; Figure 2 SEM image of the h-BN-based composite material prepared in Example 2 of this invention; Figure 3 SEM images of the h-BN-based composite material prepared in the comparative example of this invention and the porosity fluctuations in various directions are shown; (a) is the SEM image, and (b) is the porosity ratio in the x, y, and z axes. Figure 4 (a) shows the mechanical property test diagrams of the h-BN-based composite materials prepared in Example 2 and the comparative example of the present invention; (b) shows the comparison of flexural strength and (c) shows the comparison of shear strength. Detailed Implementation

[0021] The specific embodiments of the present invention are described in detail below, but it should be understood that the scope of protection of the present invention is not limited to the specific embodiments. Unless otherwise defined, all technical terms used below have the same meaning as commonly understood by those skilled in the art. The technical terms used herein are for the purpose of describing specific embodiments only and are not intended to limit the scope of protection of the present invention. Unless otherwise specifically stated, all raw materials, reagents, instruments, and equipment used in the present invention are commercially available or can be prepared by existing methods.

[0022] Example 1 This embodiment provides a rapid and efficient method for preparing continuous fiber-reinforced h-BN matrix composites, employing HP+PIP preparation technology, including the following steps: (1) Polyboron azeoline powder was ball-milled in hexane solvent at a mass ratio of 1:3 at 500 rpm for 12 h and then vacuum dried (80 °C) to obtain the raw material powder. (2) Mix the raw material powder obtained in step (1) with silicon boron nitrogen fiber cloth (size 40mm). Alternating layers (40mm) are laid up, with a total of 12 layers of fiber cloth and 13 layers of powder, each layer containing 1.5g of powder, and then pressed into shape at a pressure of 5 MPa to obtain the green body; (3) The blank obtained in step (2) was hot-pressed and sintered at 1200℃ and 30MPa. The sintering process was carried out in a nitrogen atmosphere, with a heating rate of 8℃ / min and a holding time of 3h, to obtain a preliminary dense h-BN-based composite material. (4) The preliminarily dense h-BN-based composite material was impregnated and cured once in cycloborane at 90°C for 36 hours; then it was pyrolyzed at 1300°C for 1 hour in a vacuum environment to obtain the final h-BN-based composite material.

[0023] The density and mechanical properties of the composite material prepared in this example were tested, and the density was 1.76 g / cm³. 3 The flexural strength was 90.95 MPa and the shear strength was 17.32 MPa. Compared with the composite material obtained by PIP in the same comparative example, the mechanical properties and density were significantly improved.

[0024] Example 2 This embodiment provides a rapid and efficient method for preparing continuous fiber-reinforced h-BN matrix composites, employing HP+PIP preparation technology, including the following steps: (1) Polyboron azeoline powder was ball-milled in hexane solvent at a mass ratio of 1:3 at 500 rpm for 12 h and then vacuum dried (80 °C) to obtain the raw material powder. (2) Mix the raw material powder obtained in step (1) with silicon boron nitrogen fiber cloth (size 40mm). Alternating layers (40mm) are laid up, with a total of 12 layers of fiber cloth and 13 layers of powder, each layer containing 1.5g of powder, and then pressed into shape at a pressure of 5 MPa to obtain the green body; (3) The blank obtained in step (2) was hot-pressed and sintered at 1300℃ and 30MPa. The sintering was carried out in a nitrogen atmosphere, with a heating rate of 8℃ / min and a holding time of 3h, to obtain a preliminary dense h-BN-based composite material. (4) The preliminarily dense h-BN-based composite material was impregnated and cured once in cycloborane under the curing conditions of 90℃ for 36h; then it was pyrolyzed at 1300℃ for 1h in a vacuum environment to obtain the final h-BN-based composite material.

[0025] The density and mechanical properties of the composite material prepared in this example were tested, and the density was 1.85 g / cm³. 3 The flexural strength is 108.73 MPa and the shear strength reaches 19.31 MPa. Compared with the PIP composite material obtained in the comparative example, the mechanical properties and density are significantly improved, which can effectively improve the weak interlayer bonding problem of traditional PIP.

[0026] Example 3 This embodiment provides a rapid and efficient method for preparing continuous fiber-reinforced h-BN matrix composites, employing HP+PIP preparation technology, including the following steps: (1) Polyborazane powder was ball-milled in hexane ball milling solvent at 500 rpm for 12 h, and then vacuum dried to obtain raw material powder; (2) Mix the raw material powder obtained in step (1) with alumina fiber cloth (size 40mm). Alternating layers (40mm) are laid up, with a total of 12 layers of fiber cloth and 13 layers of powder, each layer containing 1.5g of powder, and then pressed into a blank, with each layer containing 1.5g of powder. (3) The blank obtained in step (2) was hot-pressed and sintered at 1300℃ and 30MPa. The sintering process was carried out in a nitrogen atmosphere, with a heating rate of 8℃ / min and a holding time of 3 h, to obtain a preliminary dense h-BN-based composite material. (4) The preliminarily dense h-BN-based composite material was impregnated and cured in cycloborane at 90°C for 36 hours; then it was pyrolyzed at 1300°C for 1 hour under vacuum to obtain the final h-BN-based composite material.

[0027] The density and mechanical properties of the composite material prepared in this example were tested, and the density was 1.73 g / cm³. 3 It has a flexural strength of 91.2 MPa and excellent mechanical properties and density.

[0028] Comparative Example This comparative example provides a method for preparing h-BN-based composite materials using the PIP method. The h-BN-based composite material preparation method is a precursor impregnation pyrolysis method, comprising the following steps: S1. The fiber preform with the same fiber volume fraction as in Example 1 was impregnated and cured in a cycloborane precursor at 90°C for 36 hours. The fiber used was silicon boron nitride fiber. S2. The cured preform is pyrolyzed at 1300℃ for 1 hour under vacuum conditions; S3. Repeat the impregnation-curing-pyrolysis process 6 times to obtain the h-BN-based composite material.

[0029] The density and mechanical properties of the composite material prepared in this comparative example were tested, and the density was 1.62 g / cm³. 3 The flexural strength was 58.73 MPa, and the shear strength was 5.67 MPa. This comparative example required multiple impregnation-curing-pyrolysis processes, resulting in a long preparation cycle and lower density and mechanical properties in the resulting composite material.

[0030] Figure 1The figures show the XCT reconstruction images of the h-BN-based composite materials prepared in Example 2 and the comparative example of this invention. The figures illustrate the distribution of the fiber, matrix, and pore phases within the composite materials. As can be seen from the figures, the composite material prepared in the comparative example (PIP) exhibits a higher pore density and a relatively larger equivalent pore volume, morphologically displaying a connected, lamellar structure widely distributed within the sample. In contrast, the composite material prepared in Example 2 primarily contains submicron-sized pores, accompanied by a small number of crack-like pores. Comparing the matrix state of the samples prepared by the two methods reveals that the matrix phase of the composite material prepared by the method of this invention exhibits excellent uniformity and density, forming a continuous and dense filling structure between the fibers. In contrast, the composite material prepared in the comparative example shows a relatively dispersed spatial distribution of the matrix phase, with a lower volume fraction compared to the hot-pressing process, and the matrix phase contains numerous micropores, failing to form a continuous, uniform, and dense matrix network. Further quantitative statistical analysis of the segmented phases yielded the following results: Figure 1 As shown in (c), the porosity of the composite material prepared in the comparative example is 24.82%, while the porosity of the composite material obtained in Example 2 is 4.21%. This demonstrates that the composite material obtained by the method of the present invention has high density and a uniform matrix distribution.

[0031] Figure 2 The images show SEM images of the h-BN-based composite material prepared in Example 2 of this invention in various directions. As can be seen from the images, there are virtually no obvious pores between the fiber bundles in the sample; only a small number of submicron-sized intra-fiber pores exist in the gaps between the individual filaments within the fiber bundles. The matrix phase does not show differentiated distribution in the x, y, and z directions, exhibiting an overall uniform and dense state. Furthermore, the external pressure applied during the hot-pressing process plays a crucial role in regulating the fiber bundle structure and interfacial bonding. On the one hand, in the hot-pressing direction, the contact interface between fiber bundle layers is tighter, significantly reducing the formation of interlayer porosity; on the other hand, the pressure promotes the dispersion of individual fibers within the fiber bundle, increasing the contact area between the fiber and the matrix, and strengthening the fiber-matrix interfacial bonding strength.

[0032] Figure 3The images show cross-sectional scanning electron microscope (SEM) images of the composite material prepared by the comparative example (PIP) in multiple directions. The images reveal a large number of pores in all directions. Within the fiber cloth plane, the pores are classified into small circular pores and cracks. The inter-bundle pores within the fiber cloth plane originate from the initial square gaps formed by the interlocking fiber bundles in two directions. During PIP, the precursor wets and fills the pores from the fiber surface and pore edges towards the center, gradually transforming the square gaps into circular or near-circular pores. However, during this process, the precursor can only wet and spread along the pore walls and cannot completely fill the pore core region. In the subsequent pyrolysis stage, the precursor undergoes an inorganic ceramic transformation, accompanied by a 15%-30% volume shrinkage, further expanding the unfilled pore core region. Simultaneously, the pores become closed pores due to the solidification of the surrounding matrix, blocking the mass transfer channels during subsequent PIP cycles, ultimately remaining as large-sized near-circular closed pores. The formation of matrix cracks is directly related to the volumetric shrinkage effect of the precursor during high-temperature pyrolysis. During the pyrolysis stage, the volumetric shrinkage of the precursor induces internal stress. When this stress exceeds the fracture toughness of the matrix, cracking occurs. Although multiple PIP cycles can partially fill the cracks, some crack defects remain. Figure 3 (a) Within the area indicated by the yellow dashed line. In the z-direction, i.e., the fiber fabric stacking direction, there are microscopic undulations at the interlayer contact interface between adjacent fiber fabrics. When the interlayer spacing between adjacent fiber bundles is large, interlayer pores with large scales extending along the z-direction are formed. These pores have long and geometrically tortuous seepage channels, making it difficult for precursors to effectively penetrate during the PIP impregnation stage. This results in typical interlayer defects within the sample, limiting the interlayer bonding strength of the composite material. From Figure 3 (b) As can be seen, the porosity in the z-direction (thickness direction) exhibits a significant internal-external gradient, with the internal and external values ​​differing by several times. However, the differences in the x and y directions are significantly smaller. The main reason for this phenomenon is that the z-direction precursor has few, long, and tortuous flow paths, making it difficult for the precursor to penetrate into the sample's internal pores in the early stages of PIP. In the middle stage of PIP, near-surface pores are preferentially filled, further restricting the flow channels in the internal pores. Until the later stage of PIP, the unfilled pores remain as closed pores, ultimately forming a porosity gradient in the thickness direction. This non-uniformity of pore distribution directly leads to significant differences in the microstructure and mechanical and thermal properties of different regions of the PIP sample, resulting in poor overall material performance uniformity.

[0033] The foregoing description of specific exemplary embodiments of the invention is for illustrative and explanatory purposes. These descriptions are not intended to limit the invention to the precise forms disclosed, and it will be apparent that many changes and variations can be made in accordance with the foregoing teachings. The exemplary embodiments were chosen and described in order to explain the specific principles of the invention and its practical application, thereby enabling those skilled in the art to implement and utilize various different exemplary embodiments of the invention, as well as various different choices and variations. The scope of the invention is intended to be defined by the claims and their equivalents.

Claims

1. A rapid and efficient preparation method for continuous fiber-reinforced h-BN-based composite materials, characterized in that, Includes the following steps: (1) Lay out layers of fiber cloth and polyboron alkane raw material powder in a layer-by-layer manner, and then pre-press to obtain the green body; (2) The blank obtained in step (1) is hot-pressed and sintered at 1100-1300℃ and 5~35MPa pressure to obtain a preliminary dense composite material; (3) The preliminarily dense composite material obtained in step (2) is impregnated once in cycloborane, and then cured and pyrolyzed to obtain a continuous fiber reinforced h-BN-based composite material.

2. The preparation method according to claim 1, characterized in that, The polyboron azelaline raw material powder is obtained by ball milling polyboron azelaline powder in a solvent and then vacuum drying it; the ball milling speed is 400-600 rpm, the ball milling time is 10-15 h, and the particle size of the raw material powder after ball milling is < 100 nm.

3. The preparation method according to claim 1, characterized in that, The fiber cloth is made of alumina, silicon nitride, or silicon boron nitrogen fiber cloth.

4. The preparation method according to claim 1, characterized in that, In step (1), the density of the powder layer is 0.08~0.11 g / cm³. 2 .

5. The preparation method according to claim 1, characterized in that, In step (1), the pre-compression pressure is 4~7MPa.

6. The preparation method according to claim 1, characterized in that, In step (2), hot pressing sintering is carried out in a protective atmosphere. The holding time during sintering is 1-4 h, and the heating rate is 5-10℃ / min.

7. The preparation method according to claim 1, characterized in that, In step (3), after curing and pyrolysis at 90~100℃ for 30~40h, high-temperature pyrolysis at 1200~1350℃ for 0.5~1h is performed.

8. A continuous fiber-reinforced h-BN-based composite material, characterized in that, The composite material is prepared by the preparation method according to any one of claims 1 to 7.

9. The continuous fiber-reinforced h-BN-based composite material according to claim 8, characterized in that, The composite material has a fiber volume fraction of 20-30% and a density >1.7 g / cm³. 3 Flexural strength > 90 MPa, shear strength > 17 MPa.

10. The use of the continuous fiber reinforced h-BN matrix composite material as described in claim 8 or 9 in the fabrication of a transparent antenna radome or a transparent antenna window.